Chemical Principles in the Laboratory, 12th Edition - Emil J. Slowinski; Wayne C. Wolsey; Robert Rossi (Cengage Learning, 2020)
This updated 12th Edition of CHEMICAL PRINCIPLES IN THE LABORATORY maintains the high-quality, time-tested experiments and techniques that have made this student-friendly resource a perennial bestseller. Continuing to offer complete coverage of basic chemistry principles, the authors present topics in a direct, easy-to-understand manner. This edition remains committed to green chemistry and includes four experiments made ""greener"" by reducing volume and toxicity, which not only benefits the environment, but also reduces the cost of the experiments overall. This edition also includes a new experiment on the fundamental concepts of quantum mechanics. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.